2021
DOI: 10.1002/jsfa.11649
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of 4% salmon phospholipid on metabolic syndrome in mice based on colonic lipidomics analysis

Abstract: BACKGROUND The incidence of metabolic syndrome (MetS) is increasing, and n‐3 polyunsaturated fatty acids (PUFAs) in salmon (Oncorhynchus) phospholipids can effectively reduce the risk of MetS. RESULTS Under the intervention of 4% salmon phospholipid, the levels of fasting blood glucose (FBG), insulin, monocyte chemoattractant protein‐1 (MCP‐1), interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) were significantly reduced in the plasma of MetS mice, whereas adiponectin was significantly increased. By scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This means that there may be certain substances in the oil that can affect metabolic syndrome. Salmon and catfish phospholipids are rich in N-3 polyunsaturated fatty acids (PUFAs) [ 6 , 7 , 8 ], because n-3 polyunsaturated fatty acids (PUFAs) can inhibit triglyceride levels and inhibit metabolic disorders, such as cardiovascular disease and obesity, including dyslipidemia and insulin resistance, and it has been reported that the intake of n-3 polyunsaturated fatty acids (PUFAs) in the diet containing fish has a risk-reducing effect on the prevention of cardiovascular and cerebrovascular diseases, cancer, metabolic syndrome, and Parkinson’s syndrome [ 9 , 10 ]. Lipidomics is an emerging method for the comprehensive and systematic studies of multiple lipids [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This means that there may be certain substances in the oil that can affect metabolic syndrome. Salmon and catfish phospholipids are rich in N-3 polyunsaturated fatty acids (PUFAs) [ 6 , 7 , 8 ], because n-3 polyunsaturated fatty acids (PUFAs) can inhibit triglyceride levels and inhibit metabolic disorders, such as cardiovascular disease and obesity, including dyslipidemia and insulin resistance, and it has been reported that the intake of n-3 polyunsaturated fatty acids (PUFAs) in the diet containing fish has a risk-reducing effect on the prevention of cardiovascular and cerebrovascular diseases, cancer, metabolic syndrome, and Parkinson’s syndrome [ 9 , 10 ]. Lipidomics is an emerging method for the comprehensive and systematic studies of multiple lipids [ 11 ].…”
Section: Introductionmentioning
confidence: 99%